Treinamento de pais em grupo para tratamento de sintomas externalizantes em crianças com TDAH: eficácia e preditores psicopatológicos - Luciana Carla Araujo Pimenta (2014)
Introduction: The Attention Deficit/Hyperactivity Disorder (ADHD) is often associated to externalizing symptoms, resulting in personal, family, social and academic problems. The therapeutic approach to ADHD must include psychiatric drugs, psychotherapy, or the association of both. The efficacy of Parent Training (PT), a behavioral psychotherapy, is broadly described for children with externalizing symptoms. PT aims at helping parents to develop skills to deal with behavioral issues of their children. Objectives: To assess the efficacy of group-based PT for children with ADHD and externalizing symptoms in a sample of children attended at the Children and Youth Psychiatric Ambulatory of the HC-UFMG. To identify possible psychopathological and demographic predictors of the PT efficacy. Method: Children ranging from 6 to 10 years old with ADHD and externalizing symptoms referred to PT were assigned to a control group (15 children) or to a treatment group (16 children). Parents of the treatment group participated in the PT. The program used was an adaptation of the program described by Barkley, during 3 months. Parents of the treatment group answered scales of assessment of their childrens symptoms in three times (pre-treatment: T1; post-treatment: T2; and a month after completion). The parents of the control group answered in two times (T1 and T2) with intervals of three months. The Wilcoxon test was performed to analyze the efficacy of the treatment. The children and parents that participated in the therapy underwent a psychiatric assessment. The data of twenty-two children that participated in the therapy were used in the analysis of predictors of PT efficacy. Multiple linear regressions were carried out with the objective to assess the predictors of the response related to the inattention, hyperactivity/impulsivity and defiant/oppositional symptoms. Results: The treatment group presented a statistically significant difference between the pre- and post-treatment scores with the improvement of symptoms. The control group did not present any significant difference between T1 and T2. In the subsequent month, a little loss of efficacy was registered, without statistical significance. An increased improvement of the inattention symptoms was predicted by the severity of the hyperactivity symptom in T1. An increased of improvement of the hyperactivity/impulsivity symptoms was predicted by ethnicity severity of inattention in T1, by the childs age and gender. An increased of improvement of the defiant/oppositional symptoms was predicted by the number of the childs comorbidities, ethnics and severity of the externalizing symptoms in T1. CONCLUSION: PT is effective in reducing symptoms of inattention, hyperactivity/impulsivity and oppositionality/defiance in children with ADHD proven. The severity of the symptoms was predictor of a better response to treatment. The number of comorbidities of the child, being a girl, being Caucasian, and older age were predictors of the worse response.